Differentiation of K562 Cells Under ELF-EMF Applied at Different Time Courses - GARİP, GÜNSELİ AYŞE (TAYLOR & FRANCIS INC, 2010)
The time-course of ELF-EMF application to biological systems is thought to be an important parameter determining the physiological outcome. This study investigated the effect of ELF-EMF on the differentiation of K562 cells at different time courses. ELF-EMF (50 Hz, 5 mT, 1 h) was applied at two different time-courses; first at the onset of hemin induction for 1 h, and second, daily 1 h for four days. While single exposure to ELF-EMF resulted in a decrease in differentiation, ELF-EMF applied everyday for 1 h caused an increase in differentiation. The effect of co-stressors, magnesium, and heat-shock was also determined and similar results were obtained. ELF-EMF increased ROS levels in K562 cells not treated with hemin, however did not change ROS levels of hemin treated cells indicating that ROS was not the cause. Overall, these results imply that the time-course of application is an important parameter determining the physiological response of cells to ELF-EMF.
Keywords: ELF-EMF; Differentiation; Exposure time-course; Heat shock; ROS; K562; CHEMICALLY-INDUCED DIFFERENTIATION; ELECTROMAGNETIC-FIELDS; INTERMITTENT EXPOSURE; ACTIVATION; RESISTANCE; KINASE; GROWTH